REKOGNISI KEBIJAKAN PEMERINTAH TERHADAP PESANTREN SEBAGAI LEMBAGA PENDIDIKAN DI INDONESIA - Muh Mustakim (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
Pesantren is the oldest Islamic religious education institution in Indonesia. However, the regulations and recognition of the Indonesian government are not the same as the recognition of schools, why? The results of this study show that government policies and pesantren recognition are divided into five periods, namely recognition of the existence of pesantren; recognition of pesantren as religious educational institutions in Indonesia; pesantren are equivalent to school and madrasah; pesantren as part of the Indonesia education system; and the period of independent existence of pesantren as educational institutions.